2022
DOI: 10.21608/epsj.2022.263846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Levels of Biochar Supplementation as a Growth Promoter on Productive and Physiological Performance of Broiler Chicks

Abstract: This study aimed to determine the effects of graded amounts of biochar supplementation on broiler chick production index, lipid profile, biomarkers of antioxidant status, carcass characteristics, and economic efficiency. A total of 216, seven-day-old, unsexed broiler chicks (Arbor Acres) were divided into six experimental groups (36 chicks each), each with six replicates (6 chicks each). The first group was fed the basal diet and served as control; while the 2 nd , 3 rd , 4 th , 5 th , and 6 th groups were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to Mabe et al 63 , Cyprinus carpio when fed bamboo BC showed no changes in growth indices; however, their serum quality had improved, suggesting better overall fish health. Elghalid 64 found that hematological traits such as Hb, RBCs and hemocytosis percentage (HCT%) improved when chicks were given diets containing 0%, 1%, 2%, 4%, 6%, or 8% biochar. According to Dim et al 65 , when BC was given to Meleagris gallopavo (turkey) at 5 g kg −1 , 15 g kg −1 and 25 g kg −1 , 15 g kg −1 , showed significant improvements in RBC, HCT, Hb, and WBC.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mabe et al 63 , Cyprinus carpio when fed bamboo BC showed no changes in growth indices; however, their serum quality had improved, suggesting better overall fish health. Elghalid 64 found that hematological traits such as Hb, RBCs and hemocytosis percentage (HCT%) improved when chicks were given diets containing 0%, 1%, 2%, 4%, 6%, or 8% biochar. According to Dim et al 65 , when BC was given to Meleagris gallopavo (turkey) at 5 g kg −1 , 15 g kg −1 and 25 g kg −1 , 15 g kg −1 , showed significant improvements in RBC, HCT, Hb, and WBC.…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed assessments regarding the haematology of several fish species fed with biochar sources are relatively rare, emphasizing the importance of the current work. However, its effects on different animal species have been evaluated such as Elnaggar et al (2022) reported that varying amounts of biochar had a significant influence on blood parameters in broiler chicks as compared to the control. The findings are consistent with the results of Dim et al (2018), who discovered that using biochar (6%) in broiler feed substantially ( p < 0.05) boosted RBCs, WBCs, PLT and other metrics.…”
Section: Discussionmentioning
confidence: 99%